STEM Integration in 21st-Century Science Education: A Systematic Literature Review - Paramita Putri Apriyani; Ni Ketut Anggriani; Gunawan Gunawan (Indonesian, 2025)
Technological developments, digitalization, and the demands of 21st-century skills necessitate science education to be more innovative, contextual, and integrative. International reports, such as PISA, underscore the need to enhance students' higher-order thinking skills (HOTS) and scientific literacy. The integration of Science, Technology, Engineering, and Mathematics (STEM) has emerged as a relevant and effective approach. This study aims to analyze the models, strategies, trends, and challenges of implementing STEM integration in science learning through a Systematic Literature Review (SLR) of articles published between 2015 and 2025. The methodology followed the PRISMA guidelines, encompassing identification, screening, and inclusion of articles retrieved from Scopus, Web of Science, ERIC, and Google Scholar databases. From a total of 762 articles, 27 met the inclusion criteria. The results indicate that the Engineering Design Process (EDP), Project-Based Learning STEM (PjBL-STEM), Problem-Based Learning STEM (PBL-STEM), and Integrated STEM models are the most dominantly implemented and have been proven to enhance HOTS, creativity, technological literacy, scientific literacy, and problem-solving skills. Key challenges include teacher competence, limited facilities, and curriculum integration. STEM integration holds significant potential to improve the quality of 21st-century science education. These findings provide practical implications for science teachers in designing contextual, collaborative, and 21st-century skill-oriented STEM learning through the effective utilization of EDP, PjBL-STEM, and digital technologies.